How guided self-reflection improves critical thinking of nursing students in the pre-clinical stage? - Rona Cahyantari Merduaty; Aulia Addinillah Arum (Journal of Holistic Nursing Science, 2023)
Self-reflection has proven to improve clinical performance and support nursing students in formulating clinical reasoning. However, self-reflection is more commonly used during clinical placement. This study examines the effectiveness of guided self-reflection assignments in improving nursing students' critical thinking skills during practical learning at the academic stage. The research method used in this study is the single-subject experimental design by applying the Holistic Critical Thinking Scoring Rubric (HCTSR) to assess the respondent's self-reflection after performing two procedures taught in the laboratory. Twelve nursing students participated in this study in August 2022. Visual analysis is used to analyze the student's critical thinking score trend. The study indicates that 7 of 12 nursing students perform a positive trend during the procedure by improving their HCTSR score each intervention day. In general, the visual analysis displays an increasing trend from a maximum score of 3 (solid critical thinking) in the first self-reflection to a maximum score of 4 (very-strong critical thinking) in the last self-reflection. Guided self-reflection assessment and feedback effectively improve the thinking skills of nursing students undergoing practical learning at the academic stage. Concise and contextual guiding questions in writing self-reflection, specific self-reflection assessment rubrics, and lecturer feedback should be essential aspects of every nursing learning process, both at the pre-clinical and clinical stages. Keywords: Self-reflection; nursing student; students' performance; critical thinking; nursing care